Void fraction of supersonic steam jet in subcooled water - Afrasyab, Khan; Khairuddin, Sanaullah; M.Sobri, Takriff; Aini, Hussain; Ajmal, Shah; Imran Rafiq, Chughtai (Elsevier Ltd., 2016)
For most operations in process, petroleum and power industries gas-liquid two phase flows occurs, so an accurate estimation of void fraction is vital because it affects the calculations of heat and mass transfer as well as hydrodynamics. Any inaccuracy in estimation may lead to drastic incidents along with heavy monetary loss. An effort has been made here to estimate the approximate void fraction of supersonic steam jet into the sub-cooled water. Electrical Resistance Tomography (ERT) has been used for the purpose along with the Electrical Impedance Tomography and Diffuse Optical Tomography Reconstruction Software (EIDORS) to generate the conductivity scans obtained by ERT setup. Before the experimentation, for further assurance on our void fraction estimations, the measurement system has been calibrated by securing scans of heated Teflon rod of diameter 6 mm, which is approximately having the same cross-sectional surface area as the steam jet have and reported in previous studies at the same hydrodynamic conditions. Images of supersonic steam jet in subcooled water have been processed by the help of EIDORS and image processing technique. The over estimation in void fraction of Teflon rod is ranging from 46.17 to 83.44% and when it is subtracted from the total void fraction of supersonic steam jet (46.51–83.79%) at steam inlet pressure of 1.5–3.0 bar and surrounding water temperature 30–60 °C respectively, the actual void fraction of Teflon rod comes out to be ranging from 0.34% to 0.35% of the total cross-sectional area of vessel. When these results are compared with the previous studies, a close agreement has been observed between these two sets of results.